ARTISTIC-FIGURED THINKING OF THE AUTHOR-ARTIST AND STUDENT-RECEIPENTS IN THE DIMENSIONS OF MODERN LITERARY EDUCATION - Сафарян, Світлана (SWorldJournal, 2025)
The main regulatory documents in the field of education define the main competencies that should be formed in graduates of Ukrainian schools. Among them is reading competence, which is associated with artistic and figurative thinking. The article clarifie